Sistema de transporte del haz externo del sincrociclotrón de 28 MeV - Sametband, M.J.; Frazzini, N.A.; Sofía, H.M.; Erramuspe, H.J.; Ceballos, A.E.; Ferrero, A.M.J. (Comisión Nacional de Energía Atómica (CNEA), 1974)
Fil:Sametband, M.J. Comisión Nacional de Energía Atómica (CNEA). República Argentina